Taking Responsibility for Our Common Morality - Dyck, Arthur J. (Harvard theological review, 2005)
Scholars in all fields should hold themselves morally responsible for what they publish and teach. One would think that everyone would take this for granted, but Hilary Putnam, for one, has earnestly warned that we dare not. As he writes, “To-day, as we face the twenty-first century, our task is not to repeat the mistakes of the twentieth century.” He sounded this warning at the conclusion of his analysis of Jacques Derrida's philosophical works. Putnam regrets that philosophers reside among the all too numerous scholars whose publications and instruction aided and abetted the development of the “political tragedy” exemplified by the regimes of Hitler and Stalin. Derrida the philosopher counts among current scholars whose thinking raises the specter of repeating those mistakes of the twentieth century and their horrendous aftermath. Taking the renewal of philosophy as the theme for his Gifford Lectures of 1990, Putnam characterized the writings of Derrida as not only philosophically unsound, but also as dangerous and irresponsible.